Preparation of Ni@Pt core@shell conformal nanofibre oxygen reduction electrocatalysts via microwave-assisted galvanic displacement. Issue 24 (14th November 2019) - Ercolano, Giorgio; Farina, Filippo; Stievano, Lorenzo; Jones, Deborah J.; Rozière, Jacques; Cavaliere, Sara
Abstract : Ni@Pt core@shell nanofibres with controlled platinum shell thickness and Pt/Ni ratio are synthesised by an extremely fast and reproducible route, allowing their direct use as electrocatalysts. Abstract : Galvanic displacement is widely used for material preparation in high-tech and electronics industries, and in the last years has also found application for preparation of advanced electrocatalysts. Herein, the use of microwave irradiation is developed as an alternative means of energy delivery to increase galvanic exchange kinetics and significantly reduce the reaction time. By this means, Ni@Pt core@shell nanofibres with controlled platinum shell thickness and the Pt/Ni ratio are synthesised by an extremely fast and reproducible route. The reaction time is reduced 200-fold compared to the conventional thermal galvanic reaction. Furthermore, using microwave-assisted exchange, Pt forms a shell cleanly separated from the Ni core allowing their direct use as an electrocatalyst.